COVID-19 Pandemic Influence on Diabetes Management in Croatia - Cerovečki, Ivan; Švajda, Marija (Frontiers in Clinical Diabetes and Healthcare, 2021)
Aim: The study aims to investigate the effects of the COVID-19 pandemic on diabetes management and diabetes patients’ healthcare utilization patterns in Croatia. Methods: Using data contained in the Croatian diabetes registry (CroDiab), Central Health Information System of the Republic of Croatia (CEZIH), and the Croatian hospitalization database (BSO), indicators including the total number of registered diabetes patients, number of newly diagnosed diabetes cases, number of diabetes-related primary care visits and hospitalizations, and key diabetes control indicators were analyzed. Yearly values from 2017 until 2020 were compared. Results: The age-adjusted prevalence rate increased significantly from 2017 until 2019 (2017: 6,858/100,000; 2018: 7,053/100,000; 2019: 7,160/100,000). In 2020 the age-adjusted prevalence rate was 7,088/100,000, but the decrease was insignificant compared to 2019. The age-adjusted rate of new cases decreased from 2017 until 2019 (2017: 910/100,000; 2018: 876/100,000; 2019: 845/100,000), with a significant decrease in 2020 (692/100,000) compared to 2019. The number of diabetes panels increased from 2017 (117,676) to 2018 (131,815), with a slight decrease in 2019 (127,742) and a sharp decrease in 2020 (104,159). A similar trend was observed regarding the numbers of diabetes patients with panels, visits to primary healthcare providers for diabetes-related problems and diabetes patients who visited their primary healthcare provider. A slightly different trend was observed regarding diabetes-related hospitalizations. In 2017 there were 91,192 diabetes-related hospitalizations; the number decreased to 83,219 in 2018, increased again to 102,087 in 2019 and decreased to 85,006 in 2020. The number of hospitalized diabetes patients displayed a similar tendency. Conclusion: The COVID-19 pandemic has had a negative effect on the utilisation of healthcare by diabetes patients, which may have long-term consequences for their general health.